The Implementation of Surface Strategy Taxonomy Through Report Text Translation - Maria Osmunda Eawea Monny; Ni Putu Dian Indra Pratiwi (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2022)
The aims of this research is to find out grammar mistakes and obstacles in learning English through writing. Through writing, students can improve their understanding by paying close attention to the grammar and content. The implementation of CRS is meant to enhance the understanding of students of STMIK STIKOM Indonesia. And the implementation of Surface Strategy Taxonomy (SST) is done through documentation of students’ work through translation. The data source is taken from a report text in Indonesian as source language and translated it into English as target language. In order to know the benefit of SST, students are given the questionnaire to gain the data. Data collection is the results of students’ translations sheets. The results of 68 students’ translation work show that there are 98 error found in 4 kinds (errors omission, addition, mis-ordering and mis-formation) and each kind of error has its own sub-kind errors (SKE). The biggest error is omission with 39 errors (39,8%) and lowest error is mis-ordering with 12 errors (12,2%). Omission has 2 SKE, those are grammatical morpheme with 23 errors (23,5%) and content morpheme with 16 error (16,3%). Addition has 29 errors (29,6%) with SKE 16 simple errors addition (16,3%), and 13 double error addition (13,3%). Mis-ordering has 12 errors (12,2%) with SKE 4 misplacement of verbs (4,0%) and 8 misplacements of words/items (8,1%). Mis-formation has 18 errors with SKE 5 error of alternating form/ prepositions (5,1%), 6 errors of content oriented lexical/quantifiers (6,1%) and tenses with 7 errors (7,1%). There were 9 errors found in the agreement between demonstrative pronoun and noun (9,1%) and the lowest number of errors are apostrophe s and misplacement of verb with 4 errors each (4,0%). The questionnaire shows that the implementation of SST does help the students where 30 students (46,2%) said that they know their mistake, 24 students (36,9%) stated that they know about the words’ choice/diction and 11 students (16,9%) said that SST helps them to improve their English grammar. Besides, students are encouraged to practice more English in their daily.